Vascular growth factors of the placenta, apoptosis of blood neutrophils in pregnant women with post-COVID syndrome - A.V. Boichuk; Y.B. Yakymchuk; O.O. Shevchuk; Sandor G. Vari (Publishing House TRILIST, 2023)
Research objectives: to determine the activity of vascular placental growth factors, apoptosis and necrosis of neutrophils in the blood of pregnant women with post-COVID syndrome. Methods and materials. 30 pregnant women (the main group) with SARS-CoV-2, positive Ig A, M or G to SARS-CoV-2 at 30-34 weeks of pregnancy took part in the study. The control group consisted of 30 women with physiological pregnancy. Blood neutrophils were studied by flow cytofluorometry. The proportion of neutrophils that were at the stage of apoptosis and necrosis was determined. The correlation of these indicators with the uncomplicated course of the gestational process during the physiological course of pregnancy and with the development of gestational complications against the background of post-COVID syndrome was determined. In the third trimester of pregnancy, we collected blood samples to determine the effect of SARS-CoV-2 infection on placental angiogenesis. We evaluated a panel of biomarkers: vascular endothelial growth factor (VEGF), placental growth factor PlGF, and interleukin-32α (IL-32α). Results. In pregnant women of the main group with a complicated course of pregnancy accompanied by post-COVID syndrome, apoptosis was at the level of 24.30 ± 0.50% of neutrophil cells, which was significantly different from the control group (4.45 ± 0.25%) (р < 0.001). The level of late apoptosis, necrosis of neutrophils increased 4 times - from 4.20 ± 0.65 to 16.80 ± 0.54% (р < 0.001). The concentration of IL-32α in pregnant women of the control group was 67.27 ± 5.63 pg/ml. Post-COVID syndrome caused an increase in this indicator in the main group by 2.8 times compared to the control group (188.36 ± 25.22 pg/ml) (p < 0.001). In the III trimester, the concentration of VEGF reached maximum values in the main group and was 192.20 ± 10.02 pg/ml, which is 2 times higher than in the control group at the same time (95.30 ± 5.65 pg/ml), (p < 0.001). In the control group the level of PIGF at full-term pregnancy was 144.53 ± 15.55 pg/ml. In women with postpartum syndrome, PIGF significantly decreased and was 43.92 ± 4.81 pg/ml, which was only 30% of the PIGF value in women with an uncomplicated pregnancy (p < 0.001). Conclusions. The development of metabolic disorders and apoptotic changes in the placental tissue are confirmed at the morphological level in the form of destructive and necrotic changes in the microcirculatory channel of the placenta. An increase in the level of annexin-positive neutrophils and activation of the degree of neutrophil necrosis is accompanied by fetoplacental dysfunction, by violation of the balance of placental growth factors and is an important marker for predicting of fetal growth retardation in pregnant women with post-COVID syndrome.